Diálogos com o sagrado : o novo Humanismo de Mircea Eliade - Queiroz, Rodrigo Danúbio (2015)
The purpose of this research is to present the New Humanism from the thought of Mircea Eliade (1907-1986). For this, we analyze the historical context in which occurred the research and the critical position of the romanian philosopher, during which modern man was guided by a rationalizing and dessacralizing Weltanschauung, where the experience of the sacred has been reduced to a primitive dimension of human mentality. Eliade interpreted this secularizing stance as the main responsible for the existential crisis of modern man who revealed himself in trouble and the nihilism of his way of being. In this sense, the humanitarian crisis is a crisis, above all, ontological. Thus, Eliade offered a new paradigm for the development of a New Humanism, which essentially consists in rediscovering the sacred experience. However, due to the process of rationalization and abandonment of a life rhythm connected to the cosmos modern man forgot access to its roots. The output to recover from forgetfulness of being and cultural provincialism is intercultural dialogue between the West and the civilizations of the East, still marked by a religious worldview, such dialogue can only occur hermeneutically through a symbolic language capable to understand the religious universe. Thus, the problem that will guide us in this research comes down to a possible sacred experience of the contribution in the formulation of a new cultural and humanistic model in the face of a secularized civilization. Indeed, to understand the experience of the sacred, we must reflect on its own meaning, homo religiosus, and his way of being on space and "terror of History".